Adaptive Transceivers for Mobile Communications - Tiong, Tiong Teck Chai (The Institute of Electrical and Electronics Engineers, 2014)
4G LTE demands higher peak data rate and spectral efficiency. For a given bandwidth allocation, spectral efficiency can be increased by increasing data rate using higher order modulation or larger MIMO techniques. However, this can increase the probability of error in noisy channel. Therefore, this paper proposed an integrated adaptive modulation, coding and precoding for 4 X 4 broadband wireless MIMO-OFDM system. The receiver provides continuing channel state information feedback to the transmitter. The proposed system employs channel-aware scheduling techniques that can dynamically change system parameters based on channel conditions and achieve high spectral efficiencies without increasing bit error rate in noisy channels.